Migração e sobrevivência de larvas infectantes de nematódeos gastrintestinais no perfil do pasto de diferentes espécies forrageiras - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The purpose of the experiment was to evaluate infective larvae migration and survival in three forage grass species. Experimental modules constituted by plots established with: Tifton 85 (Cynodon dactylon) (experiment 1), Oats (Avena sativa L.) (experiments 2 and 3) e Ryegrass (Lolium multiflorum Lam) (experiment 3) were used in the study. Each plot was divided into 18 subplot of 30 cm², totaling 72 subplots (allowing six replicates per treatment). Migration and larval survival were evaluated up to 28 days after contamination of the experimental modules, in different plant strata (A: 50% higher, B: 25% later and C: 25% remaining), in three times (06:00, 12:00 and 18:00). In the Tifton 85 experiment was also evaluated two levels of lightness and grass height were evaluated (low shade, low sun, high shade, high sun). Feces and forage was collected seven, 14, 21 and 28 days after the deposition of feces contaminated with gastrointestinal nematode eggs in the pasture. Pasture height was measured in each subplot immediately prior to sampling. The forage of the different strata was cut from an area measuring 10-cm in radius. The faeces were manually collected and stored in identified plastic bags. The pasture, after the cutting of each strata, was transferred to previously identified paper bags. A completely randomized design was used in factorial scheme 6 (repetition) x 2 (height) x 2 (luminosity) x 3 (time) x 4 (day) in the experiment 1 and 3 (time) x 3 (stratum) x 4 ) x 6 (repeat) in experiments 2 and 3. In the first experiment the highest recovery of L3 in the pasture occurred in the D14 (low grass in the shade), followed by the D7 (low grass in the shade) and D14 (high grass in the shade) (P> 0.05). In total, were recovered 325 L3 / kg DM, 290 L3 / kg DM and 153 L3 / kg DM, from D14, D7 (low shadow) and D14 (high pasture in the shade), respectively. The maximum recovery occurred in D7 and D14, obtaining a total of 484 L3 / kg of DM and 623 L3 / kg of DM, respectively. There was no recovery of L3 in the second experiment. In the third experiment, the recovery of L3 in the pasture was small and there was no difference between the treatments (P> 0.05). A total of 893 L3 of Haemonchus spp./Kg of DM and 538 L3 of Trichostrongylus spp./Kg of DM were recovered in the module using oats, 20933 L3 of Haemonchus spp./Kg of DM and 18417 L3 of Trichostrongylus spp. / Kg DM was recovered in ryegrass module. The larvae were evenly distributed in all strata, so allowing the animal to consume only the upper stratum will not prevent the larvae ingesting, but will allow the animals to consume better fodder.
Keywords: Haemonchus spp; Horário de pastejo; Ovino; Recuperação; Trichostrongylus spp; Haemonchus spp; Time of grazing; Sheep; Recovery; Trichostrongylus spp; CNPQ::CIENCIAS AGRARIAS::ZOOTECNIA